Mycelium as metaphor: a case study of a community-based participatory research project with an oil refinery impacted community - Beltrán, Ramona; Malin, Stephanie; Hulama, Kristina; Gonzalez, Olga; Martinez, Laura (Frontiers in Environmental Science, 2025)
MethodsStandard approaches to research with communities impacted by environmental injustice often prioritizes institutions as experts rather than those with lived experience. Community-based participatory research (CBPR) emphasizes equitable and meaningful participation of community members, stakeholders, and researchers and has evolved into a widely accepted interdisciplinary methodological framework for research addressing health and social inequalities. In this case study, we use a “talk story” research dialogue between principal investigators and partner organization leaders of a non-profit that serves communities impacted by an oil refinery’s environmental pollution to reflect on relationship and implementation strategies used in the Air Quality Investigation for Research Equity (AIRE) project. Talk story utilizes dialogue and shared personal narratives to generate meaningful data through a relational process. Rooted in principles of Indigenous story work—including mutuality, reciprocal exchange, and deep relational accountability—dialogues center on a particular question or topic but unfold conversationally. Using our talk story dialogue as data, we conducted thematic analysis to illuminate the relational and concrete strategies that led to successful implementation of this CBPR project. We use mycelium as a metaphor for describing intricate mutualistic relationship-building, collaborative design, and implementation processes throughout the AIRE project.ResultsThematic analysis of the talk story dialogue revealed 5 primary themes describing the relational strategies we used from design through dissemination: 1) Rooted relationships, 2) Cultural humility and responsiveness, 3) Destabilizing power inequities, 4) Impacts of the legacy of trauma, and 5) Long term relational commitments.DiscussionDocumenting and reflecting on this CBPR project, we illustrate how embodying principles of CBPR through prioritizing building relationships of trust over time and centering community members impacted by air and environmental pollution at all stages of the research process can lead to successful research implementation and achievement of mutually beneficial shared goals. Our aim is to use this case study to develop a template of relational strategies for scholars working with and for communities impacted by environmental injustice.